Pemberian Air Rebusan Jagung (Zea Mays L) terhadap Kadar Kolesterol pada Remaja dengan Obesitas dalam Pencegahan Kegawatdarurat Kardiovaskuler - Fadlilah, Maya; Febrilia, Nia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effectiveness of corn decoction (Zea Mays L) on cholesterol levels in obese adolescents in the prevention of cardiovascular emergencies. The method used in this research is a pre-experimental design with a one group pre-post design. The results of this study indicate that the administration of corn decoction given in the morning and evening has an effect on obese adolescents with abnormal cholesterol levels, with a p-value of 0.000 < 0.05, which means H0 is accepted. The conclusion of this study is that the administration of boiled corn water in the morning and evening for one week affects the cholesterol levels of obese adolescents at the Muhammadiyah University of Palembang's Faculty of Health Sciences. Therefore, the importance of utilizing non-pharmacological measures such as consuming corn boiled water in lowering cholesterol levels. Keywords: Corn Boiled Water, Cholesterol, Obesity.